2017
DOI: 10.1177/1548051817692329
|View full text |Cite
|
Sign up to set email alerts
|

CEO Overconfidence and Ambidextrous Innovation

Abstract: While prior research has focused on the effect of CEO overconfidence on innovation, few studies have been conducted to reveal how and whether an overconfident CEO affects ambidextrous innovation, which means the simultaneous and balanced pursuit of both exploratory and exploitative innovation. By observing firms’ patenting behavior, we investigate the effect of CEOs’ psychological attribute of overconfidence on innovation ambidexterity. In addition, we examine how a firm’s governance system moderates the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 120 publications
(212 reference statements)
0
58
0
2
Order By: Relevance
“…Soon, many authors started to omit using direct measures of overconfidence, and instead used various indirect measures and proxies of overconfidence (e.g. Malmendier and Tate, 2005a, 2005b; Verberne, 2010; Jouber, 2013; Park and Chung, 2017; Wong, 2017; Choi et al , 2018; Hayward and Hambrick, 1997; Adebambo and Yan, 2016). Some of them even did not measure overconfidence and instead used excessive investment or trading as a proxy for overconfidence (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Soon, many authors started to omit using direct measures of overconfidence, and instead used various indirect measures and proxies of overconfidence (e.g. Malmendier and Tate, 2005a, 2005b; Verberne, 2010; Jouber, 2013; Park and Chung, 2017; Wong, 2017; Choi et al , 2018; Hayward and Hambrick, 1997; Adebambo and Yan, 2016). Some of them even did not measure overconfidence and instead used excessive investment or trading as a proxy for overconfidence (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wrong conclusions due to weak measures may further lead to deficient practical implications (e.g., for selection and placement of CEOs) and distort theoretical implications and frameworks that rely on findings from studies using the NI and other unobtrusive measures. This is all the more relevant since research on CEO personality in general (Araujo-Cabrera et al, 2017; Colbert et al, 2014; Wong et al, 2017), and narcissism in particular (Gupta & Misangyi, 2018; Gupta et al, 2018; O’Reilly et al, 2018; Zhang et al, 2017), continues to engender interest among researchers. Our findings also cast doubt on previous studies that showed that the NI and similar measures predict outcomes such as financial performance as it reverses the common assumption of cause and effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, measure deficiency may produce a series of subsequent failures in these studies and lead to flawed theoretical and practical implications. Deriving the right conclusions is crucial since narcissism and similar attributes of leaders are important indicators of organizational behavior and outcomes and spark interest among academic scholars (Grijalva et al, 2015; O’Reilly et al, 2018; Simonet et al, 2018; Wong et al, 2017).…”
mentioning
confidence: 99%
“…Pemilihan komisaris independen dapat menjadi faktor kunci untuk meningkatkan kinerja dewan direksi dalam mencapai inovasi. Komisaris independen akan mencegah CEO menyalahgunakan kekuasaannya terkait alokasi sumber daya untuk inovasi dan tujuan jangka panjang (Wong et al, 2017). Ada kecenderungan CEO melakukan manajemen laba riil dengan cara memotong biayabiaya terkait penelitian dan pengembangan untuk kepentingan jangka pendek, yaitu untuk mencapai target bonus.…”
Section: Keberadaan Komisaris Independen Diharapkan Dapat Mengawasi Dan Membantu Chiefunclassified
“…Inovasi merupakan suatu proses yang dilakukan secara berulang dan melalui berbagai tahapan yang mengubah ide-ide menjadi produk, jasa maupun proses yang membawa perbaikan maupun perubahan baru ke dalam suatu organisasi (Baregheh et al, 2009;Utterback, 1971;Wong et al, 2017dalam Rajeb et al, 2019 Rejeb et al, 2019). Sebagian besar literatur berfokus pada dua metode untuk mengukur inovasi, yaitu pertimbangkan input (segala upaya yang dilakukan oleh perusahaan untuk menjadi lebih kompetitif dan lebih inovatif, yang biasanya direpresentasikan oleh pengeluaran untuk penelitian dan pengembangan (R&D) sebagai persentase dari total penjualan perusahaan, atau dengan jumlah orang terlibat dalam kegiatan penelitian dan pengembangan sebagai persentase dari total karyawan perusahaan) dan hasilnya (hasil dari kegiatan inovatif diukur sebagai jumlah paten terdaftar atau masuk proses terdaftar oleh perusahaan).…”
Section: Inovasiunclassified